2005
DOI: 10.1055/s-2004-818791
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydophila PneumoniaeRespiratory Tract Infection Aggravates Therapy Refractory Bronchitis or Pneumonia in Childhood

Abstract: In children with therapy-refractory bronchitis or pneumonia bronchial C. pneumoniae infection was associated with a more severe disease in case of several, mostly bacterial co-infections. Adequate antibiotic therapy for C. pneumoniae infection has been demonstrated to improve pulmonary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Consequently, impaired defence might facilitate adhesion of further micro-organisms to the bronchial system. In children with C. pneumoniae infection, bacterial co-infections and coinfections with mycoplasmas were identified as factors often associated with purulent bronchial inflammation and restrictive disturbances of lung function leading to more severe disease [42].…”
Section: Clinical Outcome and Pathogenesis Of Chlamydial Infections Wmentioning
confidence: 99%
“…Consequently, impaired defence might facilitate adhesion of further micro-organisms to the bronchial system. In children with C. pneumoniae infection, bacterial co-infections and coinfections with mycoplasmas were identified as factors often associated with purulent bronchial inflammation and restrictive disturbances of lung function leading to more severe disease [42].…”
Section: Clinical Outcome and Pathogenesis Of Chlamydial Infections Wmentioning
confidence: 99%
“… 17 20 Of the causative pathogens, both Mycoplasma pneumoniae and Chlamydia pneumoniae are strongly associated with new-onset asthma, recurrent wheezing, refractory bronchitis, acute bronchiolitis, and asthma exacerbations in children. 18 , 21 24 It has been reported that C. pneumoniae infection is common in school-age children and the immune response to chronic C. pneumoniae infection may intercommunicate with allergic inflammation to exacerbate asthma symptoms. 15 In patients with asthma with M. pneumoniae infection, the use of macrolides may alleviate the symptoms of asthma.…”
Section: Introductionmentioning
confidence: 99%